Alcohol mixed energy drink usage and risk-taking among college students in Western New York State. Issue 6 (24th August 2022) - Graczyk, Adam M.; Leone, Lucia A.; Orom, Heather; Ziegler, Amanda M.; Crandall, Amanda K.; Klasko-Foster, Lynne B.; Temple, Jennifer L.
Abstract: Alcohol mixed energy drinks (AmED) may promote excessive alcohol intake and risk-taking among college students. Objective: To understand the relationship between AmED use and risky behavior as well as attitudes and motivations for AmED use. Participants: Undergraduate college students N = 422 (Study 1), N = 37 (Study 2). Methods: Using a mixed-methods approach, we first surveyed undergraduate students about their AmED and alcohol consumption and a series of risk behaviors, self-efficacy, and beliefs (Study 1). We then conducted focus groups within the same population to better understand attitudes, knowledge, and motivations for using AmED (Study 2). Results: Recent AmED use was significantly associated with an increased number of reported binge drinking occasions and self-reported driving while intoxicated events. Our qualitative data analyses revealed two major themes associated with AmED consumption: factors encouraging AmED use and decisions about driving while under the influence of alcohol. Conclusions: These findings add to the literature of beliefs and motivations for AmED use among college students.